Alkynes as Linchpins for the Additive Annulation of Biphenyls: Convergent Construction of Functionalized Fused Helicenes. (18th August 2016) - Mohamed, Rana K.; Mondal, Sayantan; Guerrera, Joseph V.; Eaton, Teresa M.; Albrecht‐Schmitt, Thomas E.; Shatruk, Michael; Alabugin, Igor V.
Abstract: A new approach to fused helicenes is reported, where varied substituents are readily incorporated in the extended aromatic frame. From the alkynyl precursor, the final helical compounds are obtained under mild conditions in a two‐step process, in which the final C−C bond is formed via a photochemical cyclization/ dehydroiodination sequence. The distortion of the π‐system from planarity leads to unusual packing in the solid state. Computational analysis reveals that substituent incorporation perturbs geometries and electronic structures of these nonplanar aromatics.